MENGEMBANGKAN KEMANDIRIAN DAN MOTORIK HALUS PADA SISWA DOWN SYNDROME DI SEKOLAH LUAR BIASA (SLB) - Lilik Fadlilatin Azizah; Mas'odi Mas'odi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2020)
Down Syndrome is a condition of underdevelopment of physical and mental development in children caused by chromosomal development abnormalities. At her age which have entered adolescence her mother always serve Subjects in all daily activities. Subjects, in dressing Subject was also still assisted by his mother. After given the handling on the subject, then got satisfactory results. Independence on the subject has begun to develop, the subject at home was not willing to be bathed again, when the bath time the subject will ask for toiletries and then bathed himself, and after bathing, the subject will use his own clothes, but the clothes still need to be prepared before. This research uses research with qualitative of case study. This research data form of interview result, observation result and written sources. The data were collected using interview and observation techniques. The data analysis activity is done by thematic analysis.